The Good Prison Officer: Inside Perspectives - Brierley, Andi (Taylor & Francis Group, 2023)
Cover -- Half Title -- Endorsements -- Title Page -- Copyright Page -- Contents -- Contributors -- Disclaimer -- Acknowledgements -- Foreword -- Preface -- Abbreviations -- 1. An Introduction to the Team and Project -- 2. The Legitimacy of Trust -- 3. More Than a Number! -- 4. Flexibility: Negotiation and Discretion -- 5. I Have Never Met a Child That Healed in a Cell -- 6. From Adversity to University -- 7. We're Only Human -- 8. Relationships Are the Agents of Change -- 9. Time for Change -- Afterword -- Index.